The Effect of Hots-Oriented Worksheets with Barcode Assistance in Online Learning on Critical Thinking and Creatives of Students of Class XI SMAN 1 HARAU - Trio Junira Fernando; Yenni Darvina; Silvi Yulia Sari; Letmi Dwiridal; Fanny Rahmatina Rahim (Universitas Negeri Padang, 2021)
This study aims to see the effect of hots oriented job sheets with barcode assistance in online learning to the students' critical and creative thinking on heat and the kinetic theory of gases learning topic in grade xi of 1st harau district senior high school. This type of research is a quasi-experiment with a randomized only control group design. This study involved two classes, the first class as the experimental class using hots-oriented job sheets with barcode assistance and the second class as the control class. Data collection techniques in the form of a written test with a graded essay question model. The assessment is based on observable indicators of critical and creative thinking skills. data analysis using qualitative descriptive analysis techniques. The results showed that there was an increase in the ability to think critically and creatively. the experimental class was 57% and the control class was 12%. Based on the research results it can be concluded that: First, after implementing HOTS-oriented worksheets assisted by barcodes in online learning, there was an increase in students' critical thinking skills and creative skills in the experimental class. Second, there is a significant difference in the improvement of students' critical and creative thinking skills in the experimental class after implementing HOTS-oriented job sheets assisted with barcodes in online learning compared to the control class that did not apply the job sheets. Third, HOTS-oriented worksheets assisted with barcodes are very suitable to be applied in schools with an online learning system because they can improve students' critical thinking skills and creative thinking skills on heat material and the kinetic theory of gases.